ALPPS readdresses the management of advanced liver tumors - Huang, Fa-guang; Xiao, Jiang-Hua; Kong, Jun; Gong, Jian Ping (International Surgery Journal, 2017)
Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) has been developed to induce rapid liver hypertrophy of the future liver remnant (FLR) prior to hepatectomy in primarily non-resectable or marginally resectable liver tumors. In recent years, this novel strategy has aroused interests of many liver surgeons. Its indications have been broadened gradually with more and more reported cases. Modified ALPPS is also developed to reduce morbidity and mortality. The authors searched Medline and PubMed to identify related articles published in English, using terms: “ALPPS, associating liver partition and portal vein ligation for staged hepatectomy, in situ split, in situ splitting, liver partition”. The authors summarized and analysed the superiority, indications, modifications, safety, mechanisms of regeneration of ALPPS. ALPPS was more effective than traditional portal vein embolization (PVE) or portal vein ligation (PVL). ALPPS obtained 80% volume increase of future liver remnant (FLR ) within 7 days in contrast to 10%-46% within 2 to 8 weeks by PVE or PVL. ALPPS opens a chapter in the history of liver surgery and readdresses the management of advanced primary and metastatic liver tumors. The high morbidity and mortality associated with ALPPS could be decreased remarkably if we carefully select patients and carry out the operation with experienced surgeons. In addition, the safety, mechanisms and oncological outcome of ALPPS are still not clear, which need further research and randomized controlled trials.